University Access and Social Justice - Hlalele, Dipane (South African Journal of Higher Education, 2016)
This article provides an analysis and critique of contemporary practices and debates concerning inclusion and university access programmes from a social justice perspective. Agarwal, Epstein, Oppenheim, Oyler and Sonu (2010:238) indicate that social justice has “proliferated in education in recent years and is an umbrella term encompassing a large range of practices and perspectives”. It has become evident that students in some quarters of the education system frequently experience ‘negative and inequitable treatment’ (Brown, 2006; Ladson-Billings, 1994). Inclusion calls for students never to be seen in isolation from the broader societal changes and constitutional imperatives (Coates, 2007; Alexander, 2009). According to Bornman and Rose (2009), what is central to the understanding of inclusion is the notion of participation. The article addresses and examines university access programmes as social structures and institutional contexts or spaces with specified rules and regulations. Some of these rules are clearly known and well articulated; others are not so clear, whilst some are largely invisible. These institutional rules govern students’ behaviour, their thoughts and the shape of their lives.